Induction of Caspase-2 Activation by a DNA Enzyme Evokes Tumor Cell Apoptosis - Kim, Soo-Hyun; Dass, Crispin (Mary Ann Liebert, Inc. Publishers, 2012)
Caspase-2 is an enigmatic caspase that is now increasingly being associated with certain types of cell death in cells exposed to cytotoxic agents. It is now known that in some cases of cell stress, such as DNA damage, activation of this caspase is triggered, sometimes in the absence of activation of both the intrinsic and extrinsic pathways of apoptosis. Part of the reason for this enigma has been lack of a suitable stimulus for this caspase, and with the discovery of DNAzyme 13 (Dz13), a potent oligonucleotide-based caspase-2 activator, much more can now be elucidated. For instance, one thing that could be unravelled is whether caspase-8 and Fas (CD95)-associated protein with death domain are indeed involved in caspase-2 activation as part of the death-inducing signaling complex. It is also becoming apparent that this enigmatic caspase may be important in the mechanisms behind which chemotherapeutic agents inhibit tumor cell growth. A better understanding of the true biological effects of this enzyme may indeed lead to more effective ways of managing tumors clinically. This review article briefly examines the different compounds capable of inducing activation of caspase-2 and proposes Dz13 as one that will be valuable for evaluation of the biological functions of caspase-2.